Актуалізація назв літер та їхніх похідних у релігійному стилі - Соболь, Лілія; Sobol, Liliia (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті йдеться про те, що Біблія – джерело популяризації семантизованих назв букв, а релігійний стиль загалом відзначається частотністю таких одиниць. Вони поширені насамперед у назвах букв грецького алфавіту, а не кирилиці. З’ясовано, що літери та графіка використовуються для прямої номінації об’єктів, творення тропів і фігур, графічного текстового оформлення, моделювання жанрової своєрідності релігійних текстів, їхньої прагматики. Описана специфіка функціонування фразеологічних одиниць зі складниками – назвами літер у релігійному стилі. The article highlights the problem of actualization of the letter names and their derivatives in the religious style and proves that it is the Bible that is the source of popularization of the lexicalized and sematicized names of the letters. From the Bible they penetrate and adapt themselves into everyday Ukrainian, that is why modern sermons are full of lexicalized and semanticized names of letters. The author also states that the phraseological units with the names of the letters mainly belong to the biblical texts. It has been clarified that the names of the Greek letters, not the Cyrillic ones, are actualized. This process has been determined by historical conditions. In fact, the term «letter» as well as its derivatives (literally, in letters,) has been always widely used in the religious style. The names of the letters are used for both nominating and forming pragmatic meanings (the nomination of objects, the formation of a great variety of tropes and figures, the genre peculiarity and a graphic design of the text). Special attention has been drawn to the fact that the lexicalized and semanticized graphemes and idioms containing them, are transferred into other styles of the language from the religious sources.
Actualization of Letter Terms and Their Derivatives in Religious Style
Keywords: назви літер; Біблія; графіка; семантизовані та лексикалізовані графеми; номінація; релігійний стиль; names of letters; Bible; graphics; lexicalized and semanticized graphemes; nominations; religious style